The business case for quantum computing - Bova, Francesco; Goldfarb, Avi; Melko, Roger (MIT Sloan Management Review, 2023)
Much of the quantum research community is focused on showing quantum advantage — that a quantum computer can perform a calculation that is impossible on a classical computer. The authors contend that enterprises should focus instead on seeking opportunities for quantum economic advantage — when a quantum computer provides a commercially relevant solution faster than a classical computer could, or when a quantum computer provides viable solutions that differ from what a classical computer yields.